2014
DOI: 10.1111/jan.12374
|View full text |Cite
|
Sign up to set email alerts
|

A repeated measures study of changes in health‐related quality of life during pregnancy and the relationship with obstetric factors

Abstract: The results revealed the dynamic pattern of perceived health status by the Taiwanese pregnant women in their surrounding socio-cultural context and identified the stage of pregnancy and obstetric factors predicting health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
50
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 58 publications
18
50
2
Order By: Relevance
“…were effective on quality of life. It was determined that risk factors in obstetric history have had an negative impact on the quality of life [17]. In this regard, the data in our study supports the study of Chang et al [17].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…were effective on quality of life. It was determined that risk factors in obstetric history have had an negative impact on the quality of life [17]. In this regard, the data in our study supports the study of Chang et al [17].…”
Section: Discussionsupporting
confidence: 82%
“…[12], it was found that physical role and social function subscale scores were higher than other subscale scores. Chang et al [17] reported mental health average score as highest in pregnancy, Sonmezer et al [18] and Kartal and Sayiner [19] reported general health average score as highest in pregnancy. Research data show that pregnant women feel better about themselves, especially in terms of physical function, general and mental health, and are satisfied with these aspects of their lives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations